Ed. N. for "Sustaniable Aquatic Research" - Can, Erkan (Sustainable Aquatic Research, 2022)
How sustainable is sustainable living without sustainable aquatic research? Our academic journal, "Sustaniable Aquatic Research", which aims to contribute to raising awareness for sustainable life by bringing sustainable aquatic research together, has started its publication life. The subjects that make up the scope of SaquaRes have been carefully selected to serve this purpose, and have been designed with the thought that they will contribute to more sustainable life on our planet. I would like to thank all researchers and readers who have sent or will send articles to SAquaRes, who have visited or will visit the journal site, and especially those who contributed to the formation, emergence, and development of this idea. As the SAquaRes team, we promise that we will dedicate all our energies to the journal to reach its goal. "Sustainable life in the world will be realized with sustainable aquatic research"